What is the relationship between post-traumatic stress disorder, extreme appraisals of internal state and symptoms in bipolar disorder?. Issue 1 (22nd January 2020) - Frost, Laura; Mansell, Warren; Varese, Filippo; Tai, Sara
Abstract: Background: It is important to understand the factors associated with more severe mood symptoms in bipolar disorder. The integrative cognitive model of bipolar disorder proposes that extreme appraisals of changes to internal states maintain and exacerbate mood symptoms. Aims: The current study aimed to investigate if post-traumatic stress disorder (PTSD) is related to current depressive and manic bipolar symptoms, and whether this relationship is mediated by appraisals of internal state. Method: Participants with bipolar disorder ( n = 82) from a randomized controlled trial of cognitive therapy for bipolar disorder (the TEAMS trial) completed self-reported questionnaires assessing appraisals of internal state, generalized anxiety symptoms, and self-reported and observer-rated depressive and manic symptoms. Clinical interviews assessed PTSD co-morbidity. Results: Participants with bipolar and co-morbid PTSD ( n = 27) had higher depressive symptoms and more conflicting appraisals than those without PTSD. Regression analyses found PTSD to be associated with depressive symptoms but not manic symptoms. Conflicting appraisals were found to be associated only with manic symptoms meaning that the planned mediation analysis could not be completed. Conclusions: Findings provide partial support for the integrative cognitive model of bipolar disorder and highlight the need for transdiagnostic treatments in bipolar disorder due to the prevalence and impact of trauma and co-morbidity. Working on trauma experiences in therapy may impact on depressive symptoms for those with bipolar disorder and co-morbid PTSD.